“Religious freedom before, during and after covid-19 Between Europe and the Member States”: Introduzione alla prima sezione dello special issue (Stato, Chiese e pluralismo confessionale, 2022)
This contribution introduces the special issue and focuses on the content of its first section, including contributions by Javier Martínez-Torrón (and related comments by Pierluigi Consorti), Maksymilian Hau, Valerio D’Alò, Giuseppina Scala and Matteo Giannelli.